2021
DOI: 10.3390/nano11010229
|View full text |Cite
|
Sign up to set email alerts
|

Single and Repeated Applications of Cerium Oxide Nanoparticles Differently Affect the Growth and Biomass Accumulation of Silene flos-cuculi L. (Caryophyllaceae)

Abstract: Cerium oxide nanoparticles (nCeO2) have a wide variety of applications in industry. Models demonstrated that nCeO2 can reach environmental compartments. Studies regarding the relationships between plants and nCeO2 considered only crop species, whereas a relevant knowledge gap exists regarding wild plant species. Specimens of Silene flos-cuculi (Caryophyllaceae) were grown in greenhouse conditions in a substrate amended with a single dose (D1) and two and three doses (D2 and D3) of 20 mg kg−1 and 200 mg kg−1nCe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The characteristics of nCeO 2 , plant materials and the experimental design were set up as described in a previous study 34 and are summarized in Fig. 1.…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of nCeO 2 , plant materials and the experimental design were set up as described in a previous study 34 and are summarized in Fig. 1.…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
“…At 60 days from DSE, all plants were harvested. The nCeO 2 doses were chosen on the basis of previous results, 34 which demonstrated that 200 and 400 mg kg −1 were found to be the Environmental Science: Nano Paper most effective in affecting plant growth parameters, with a shortage in biomass of roots and stems, and in nCeO 2 translocation towards aerial plant fractions. The purpose of this protocol was to simulate conditions closer to reality, where plants are probabilistically exposed to CeNPs over a more extended period, at relatively lower concentrations, but through repeated pulses.…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained in one of the reviews included in this Special Issue, the number and quantity of nanomaterials is ever increasing and affecting the environment where humans, bacteria, and plants live, and their genome come in contact with nanomaterials [3]. Although the topic of genotoxicity induced by nanomaterials is important, we had only five contributions for this Special Issue: [3][4][5][6][7][8]. Marmiroli et al, 2022 [3], contributed a minireview on the methods used to analyze genotoxicity in plants.…”
mentioning
confidence: 99%
“…Lizzi et al, 2021 [4], studied the effects of multiple applications of CeO 2 oxide nanoparticles on a wild plant, Silene flos-cuculi, instead of a classical crop or model plants. They measured the quantity of nanoparticles in the plants utilising a spICP-MS (Single Particle ICP-MS), and other parameters related to the plant biomass.…”
mentioning
confidence: 99%